Tata kelola lembaga pendidikan islam non-formal: studi kasus pengelolaan madrasah diniyah al-hikam malang - Mauludya, Dita (Maliki Interdisciplinary Journal, 2026)
Madrasah Diniyah (Madin) as a non-formal Islamic educational institution faces complex challenges in governance in the contemporary era, especially related to sustainability and quality improvement. This study analyzes governance practices at Madrasah Diniyah Al-Hikam Malang, focusing on institutional aspects, learning, and supporting and inhibiting factors. The method used is qualitative with a case study approach, through observational data collection techniques, in-depth interviews with one key teacher, and document analysis. The results of the study show that the institutional governance of these madrassas already has a clear organizational structure and transformative leadership, but still relies on traditional financing. In the learning aspect, madrasas apply the classical-privat-kalisak model and the innovative Arba'in method, although the variation in teachers' competencies in technology is an obstacle. The main supporting factors lie in social capital and community commitment, while the main inhibiting factors are structural financial limitations and teacher competency gaps. It was concluded that strengthening governance requires a strategy of financial independence, sustainable teacher capacity development, and strengthening the communication system with parents. These findings provide practical contributions for madrasah managers and policy implications for non-formal Islamic education stakeholders.